2005
DOI: 10.1007/s00213-005-2145-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the protein kinase C inhibitor, staurosporine, on the high dose of methamphetamine-induced behavioral sensitization to dizocilpine (MK-801)

Abstract: These results suggest the involvement of increased glutamate levels and an activation of PKC in delayed-induced synaptic and cellular plasticity underlying the higher dose of METH-induced behavioral sensitization to dizocilpine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies have indicated that glutamate is involved in Meth behavioral sensitization (Fang et al 2005;Vanderschuren and Kalivas 2000). We recently reported that Meth induces a rapid increase in Ca ++ influx in neuronal cells overexpressing gCaMP5, an intracellular Ca ++ probe.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have indicated that glutamate is involved in Meth behavioral sensitization (Fang et al 2005;Vanderschuren and Kalivas 2000). We recently reported that Meth induces a rapid increase in Ca ++ influx in neuronal cells overexpressing gCaMP5, an intracellular Ca ++ probe.…”
Section: Discussionmentioning
confidence: 94%
“…Our group recently found that treatment with a PKC inhibitor, staurosporine, 120 min after high-dose METH injection (2.5 mg/kg) blocked METH-induced crosssensitization to MK-801, but not sensitization to METH (Fang et al 2005). Chronic administration of VPA decreases PKC activity and levels of the PKC alpha and epsilon subunits (Chen et al 1994).…”
Section: Discussionmentioning
confidence: 97%
“…As discussed previously (Ito et al 2004;Fang et al 2005), this higher dose of METH (2.5 mg/kg) delays increases in Glu levels and may induce neuroplastic changes that are related to cross-sensitization to MK-801. Taking these findings into account, the present study hypothesized that posttreatment with VPA would inhibit the METH-induced delayed increases in Glu levels in the NAC; this inhibition would block high-dose METH-induced cross-sensitization to MK-801.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations